Microscopic quasiparticle-phonon model in the study of the beta decay of Cd-115 - Haaranen, Mikko (2013)
This master’s thesis concerns the use of the microscopic quasiparticle-phonon model in the study of the beta minus decay of Cd-115. The first part of this text concentrates on the theoretical description of nearly spherical open-shell odd-A nuclei by using the microscopic quasiparticle-phonon model. The treatment of the subject is far from exhaustive but all the necessary relations needed in the practical application of the formalism are provided in the text.